Dual-protective nano-sunscreen enables high-efficient elimination of the self-derived hazards. (March 2020) - Yu, Bin; Ai, Kelong; Lu, Lehui
Graphical abstract: A novel dual-protective sunscreen nanoparticles (DSNPs) is developed to simultaneously combat the inherent defects of sunscreens. The antioxidants-wrapped sunscreen cores are encapsulated into aldehyde-functionalized outer silica shell, which can not only drastically scavenge self-generated ROS, but also achieve strong attachment with the skin surface. It opens a new dimension for the rational design of next-generation sunscreen with minimal side effects. Highlights: Dual-protective sunscreen nanoparticles (DSNPs) were designed to simultaneously overcome self-derived safety hazards. Prominent ROS scavenging efficiency of DSNPs reaching 97.8 % was achieved in the most highly toxic hydroxyl radicals. DSNPs could firmly adhere onto the outmost stratum corneum on the skin surface. DSNPs integrated UV-protective, ROS-eliminating, bioadhesive, aesthetic and biocompatible properties in one platform. Abstract: The serious health risk of sunscreens is mainly attributed to the self-induced damages. Not merely spontaneously generate deleterious reactive oxygen species (ROS), sunscreens also can penetrate through the skin and enter the body, resulting in a series of detrimental effects. Although numerous attempts have been made to remove these risks, safety hazards from sunscreens have not been fully overcome yet. Mainly because almost all of the currently proposed strategies are limited to address only one issue-either the restriction of self-generated ROS or improvement of retention. Here, we integrate the two issues as a whole, enabling us to develop a novel dual-protective sunscreen nanoparticles (DSNPs) to combat the above inherent defects of sunscreens at the same time. The antioxidants-wrapped sunscreen cores are encapsulated into aldehyde-functionalized outer silica shell, which can not only drastically scavenge self-generated ROS, but also achieve strong attachment with the skin surface. We validate the ultra-high efficiency of this dual-protective strategy through a series of in vitro and in vivo experimentations. Specifically, the DSNPs achieve the most efficient scavenging efficiencies of self-generated ROS and are efficiently prevented from entering the body. This dual-protective sunscreen opens a new dimension for the rational design of next-generation sunscreen with minimal side effects.